Mucoadhesive Chitosan Derivatives as Novel Drug Carriers - Ariful Islam, Mohammad; Park, Tae-Eun; Reesor, Emma; Cherukula, Kondareddy; Hasan, Anwarul; Firdous, Jannatul; Singh, Bijay; Kang, Sang-Kee; Choi, Yun-Jaie; Park, In-Kyu; Cho, Chong-Su (Current Pharmaceutical Design, 2015)
Chitosan on its own is a well-established natural polymer and is widely regarded as a biodegradable, biocompatible and nontoxic material for drug delivery applications. Although unmodified chitosan has some mucoadhesive properties on its own, its bioavailability is limited due to its short retention time in the body. Moreover, the high solubility of chitosan at acidic pH levels limits its use for mucosal drug delivery (especially through the oral route). Chemically-modified mucoadhesive chitosan, especially thiolated chitosan, has arisen as an alternative to create novel mucosal drug delivery systems. The mucoadhesive properties that are conferred to the thiolated chitosan certainly set this novel class of second or third-generation thiomers apart. To understand the significance of mucoadhesive chitosan, we first present the mechanism of mucoadhesion and provide comprehensive coverage of description of a variety of chemical modifications to prepare mucoadhesive thiolated chitosan derivatives. We then present the plethora of applications of these modified chitosan variants in a wide range of drug delivery fields, including the delivery of antigens, proteins and genes through a variety of routes, including oral, nasal, pulmonary, vaginal and others. By presenting the range of applications for mucoadhesive chitosan drug carriers we herein demonstrate that chemically-modified thiolated chitosan is a versatile and effective material for a new class of drug delivery vehicles.
Keywords: drug delivery